2012
DOI: 10.1242/dev.074567
|View full text |Cite
|
Sign up to set email alerts
|

Specialisation within the DWARF14 protein family confers distinct responses to karrikins and strigolactones in Arabidopsis

Abstract: SUMMARYKarrikins are butenolides derived from burnt vegetation that stimulate seed germination and enhance seedling responses to light. Strigolactones are endogenous butenolide hormones that regulate shoot and root architecture, and stimulate the branching of arbuscular mycorrhizal fungi. Thus, karrikins and strigolactones are structurally similar but physiologically distinct plant growth regulators. In Arabidopsis thaliana, responses to both classes of butenolides require the F-box protein MAX2, but it remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

30
779
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 476 publications
(813 citation statements)
references
References 55 publications
30
779
4
Order By: Relevance
“…1) (reviewed in Beveridge and Kyozuka 2010). In short, the first step of strigolactone biosynthesis involves the conversion of all-trans-β-carotene to 9-cis-β-carotene that is mediated by D27 (Waters et al 2012). Next, plastidic carotenoid cleavage dioxygenases 7 and 8 (CCD7 and CCD8 encoded, respectively, by MAX3 and MAX4 in Arabidopsis; Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) (reviewed in Beveridge and Kyozuka 2010). In short, the first step of strigolactone biosynthesis involves the conversion of all-trans-β-carotene to 9-cis-β-carotene that is mediated by D27 (Waters et al 2012). Next, plastidic carotenoid cleavage dioxygenases 7 and 8 (CCD7 and CCD8 encoded, respectively, by MAX3 and MAX4 in Arabidopsis; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1) produce carlactone (Alder et al 2012). Carlactone (or another derived intermediate) is then transported to the cytosol where it is possibly converted to strigolactones by MAX1 that encodes a cytoplasmic cytochrome P450 enzyme (Booker et al 2005;Waters et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…S1b). In addition, studies on a set of branching mutants of some plant species have indicated that the d14 and d3/max2/rms4 genes are closely related to a pathway downstream of SLs 1,2,13,14 ( Supplementary Fig. S1b).…”
mentioning
confidence: 99%
“…D14 genes encode a/b-hydrolase family proteins [13][14][15][16] and their mutants exhibit a highly branched phenotype and are insensitive to SLs [13][14] . The d3/max2/rms4 mutants are also SL insensitive 1,2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation